Discovery of novel sphingosine kinase 1 inhibitors via structure-based hierarchical virtual screening. Issue 3 (21st October 2014) - Wang, Xiaojian; Sun, Chenbin; Fang, Liang; Yin, Dali
Abstract : Hierarchical structure-based virtual screening against the sphingosine kinase 1(SphK1) binding pocket was performed. 25 compounds were selected for biological evaluation. Compound25 exhibited comparable SphK1 and SphK2 inhibitory activities and anti-proliferative effects on U937 cells to the positive control N, N -dimethylsphingosine (DMS)1 . Further molecule dynamic (MD) simulations revealed the binding mode between SphK1 and25 . Abstract : Sphingosine kinase 1 (SphK1) is an oncogenic lipid kinase, emerging as a novel and promising target for cancer and other diseases. Herein, hierarchical structure-based virtual screening against the sphingosine kinase 1(SphK1) binding pocket was performed. Consequently, three compounds have been identified as dual inhibitors of SphK1 and SphK2. Among them, compound25 exhibited comparable SphK1 and SphK2 inhibitory activities to the positive control N, N -dimethylsphingosine (DMS)1, and exerted anti-proliferative effects on U937 cells. Furthermore, molecule dynamic (MD) simulations have been conducted to provide a more detailed insight into the binding model between SphK1 and25 in a state close to physiological conditions.25 may serve as a potential novel scaffold for further development of SphK1 inhibitors.